Teachers Perceptions Of The Merdeka Curriculum’s Effects On English Proficiency Of Students - Uun Apriana Lago; Darmawan Darmawan; Ma’fulah Ma’fulah; Wahyudin Wahyudin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to explore English teachers’ perceptions of the Merdeka Curriculum and to examine its perceived impact on students’ English proficiency at SMPN 2 Palu. Specifically, the study seeks to understand how the implementation of the Merdeka Curriculum influences classroom practices, student engagement, and language learning outcomes, as well as to identify the challenges faced by teachers during its implementation. Employing a qualitative phenomenological approach, this research investigated the experiences of three English teachers who had implemented the curriculum for more than one year. Data were collected through semi-structured interviews and triangulated with students’ midterm English examination scores to enhance the validity of the findings. The results indicate that teachers perceive the Merdeka Curriculum as beneficial in promoting student-centered learning, increasing students’ speaking confidence, and encouraging collaborative learning. Nevertheless, several challenges were reported, including limited technological resources and difficulties in shifting from traditional teaching approaches. To address these issues, teachers adopted strategies such as differentiated instruction and peer tutoring. This study provides valuable insights into the influence of curriculum reform on English language teaching and offers recommendations for improving teacher training, resource availability, and curriculum implementation strategies.